Analysing partnerships and strategic network governance. (5th February 2008) - Kohtamaki, Marko; Vuorinen, Tero; Varamaki, Elina; Vesalainen, Jukka
Networks as organisational forms have achieved increasing attention in recent years. Typically, discussions have focused on the efficiency of different organisational modes, such as markets, hierarchy and networks. In this research, we argue that the economic system, when organised as networks, is often governed by using three different governance mechanisms: price, authority and trust, simultaneously. The main objective of this research is to develop the method for analysing the different mechanisms of governance in a strategic network. We apply a single case-study method to illustrate the usefulness and importance of the analysis. The analysis of governance allows managers to systematically evaluate the present and future state of partnerships in strategic networks.